(the Basic Motor Skills In Sports Activity And It's Relationship With Attention Deficit Hyperactivity Disorder (adhd - Nacerbey Karima .,; Benabderrahmane Sidali ., (sports creativity, 2025)
ADHD is one of the developmental behavioral disorders prevalent in the child's psychological nervous system, in which the child tends to lose attention and concentration, as well as excessive and unbalanced movement and impulse without thinking, and this is evident in many areas of life Including motor activities, as this disorder is likely to be related to the basic motor skills of the child, including transitional, non-transitional or dealing with the tool, This study aimed to identify the relationship between ADHD and Fundamental motor skills, the study was conducted on a sample of 35 students of primary school, using the descriptive correlational method, It was concluded that there is an inverse correlation between the dimensions of the scale of ADHD and some Fundamental motor skills.